ENFORCEMENTS AND OFFENCES UNDER THE STRATA MANAGAMENT ACT - Ahmad Shuhaimi, Ainul Ashiqin; Mohamed Osman, Mariana; Rabe, Suzilawati; Syed Khuzzan Alhabshi, Sh. Mazlina; Aripin, Damira (PLANNING MALAYSIA, 2022)
The rise in the number of strata residential buildings calls for the need for enforcement of governance relating to the wellbeing of strata residents as well as its management. The establishment of Management Body at the stage of Joint Management Body as well as the Management Corporation are both results of the enforcement of the Strata Management Act, that requires their registration with the Commissioner of Buildings (COB) to be given the rights to collect, manage and maintain the assigned residential strata properties. The aim of this study is to identify the most common issues occur under the legislation of strata management that results in the interference and enforcement by the COB, as replicated through to the number of enforcements taken by the COB. The result of the study shows that despite the enforcement of the Strata Management Act over the years, there are still a significant number of enforcement actions by the COB against the reported offences made with regards to the rights of both the residents as well as the management bodies. The constant rate of actions taken proves that there are still rooms for improvements within the Strata Act 757 itself to reduce issues, towards a more enforceable roles, standards and rules for future reference and service quality.